Efficacy and safety of SHEN26, a novel oral small molecular RdRp inhibitor for COVID-19 treatment: a multicenter, randomized, double-blinded, placebo-controlled, phase II clinical trial - Jiangtao Bai; Tetsuya Asakawa; Wenfang Yuan; Yuanlong Lin; Hao Ju; Dandan Xu; Mingming Yang; Shuo Li; Guanguan Li; Deyin Guo; Hongzhou Lu; Xumu Zhang (Virology Journal)
Abstract Background SHEN26 (ATV014) is an oral RNA-dependent RNA polymerase (RdRp) inhibitor with potential anti-SARS-CoV-2 activity. Safety, tolerability, and pharmacokinetic characteristics were verified in a Phase I study. This phase II study aimed to verify the efficacy and safety of SHEN26 in COVID-19 patients. Methods This was a multicenter randomized double-blind placebo-controlled study. Mild-to-moderate adult patients with COVID-19 were recruited and randomly assigned to the high-dose (400 mg), low-dose (200 mg), or placebo groups (1:1:1). The primary outcome measure was “changes in RNA levels on Day seven (D7)”. The second outcome measures were “changes of RNA levels on D3, D5, D10, D28,” “Time of clearance of virus.” Results A total of 91 patients were recruited in this study between December 08, 2022, and January 27, 2023. Twelve patients dropped out due to a lack of examination results. Finally, the data of 79 patients (24 in the placebo group, 31 in the 200 mg group, and 24 in the 400 mg group) were analyzed. No significant differences in the baseline data were observed between the groups. The changes of viral load were significantly higher on D3 (P = 0.0119), and D5 (P = 0.0120) in 400 mg group (vs. placebo group), and the difference value achieved 1.06 log10 copies/mL on D3 and 1.21 log10 copies/mL on D5. No significant difference was found in the viral clearance time between SHEN26 administrating groups and placebo groups. Administration of SHEN26 did not enhance drug-related ADEs and did not induce ADEs, and ADE inducing drug withdrawal, dose reduction, or death. Moreover, SHEN26 did not worsen the renal function. Conclusions Our findings indicate a better efficacy of a high dose (400 mg) for COVID-19 treatment. These preliminary data on the efficacy and safety provide useful information and a working basis for further verification and development of SHEN26 as a novel oral small-molecule antiviral drug for treating COVID-19.